Functional and Genomic Analysis of Rouxiella badensis SER3 as a Novel Biocontrol Agent of Fungal Pathogens - Morales-Cedeño, Luzmaria R.; de los Santos-Villalobos, Sergio; Santoyo, Gustavo (Frontiers in Microbiology, 2021)
In recent decades, various bacterial species have been characterized as biocontrol agents for plant crop diseases; however, only a few genera have been predominantly reported in literature. Therefore, identification of for new antagonists against phytopathogens is essential for boosting sustainable food production systems. In this study, we evaluated the role of strain SER3 from the recently discovered Rouxiella badensis as a biocontrol agent. SER3 was isolated from the phyllosphere of decaying strawberry fruit (Fragaria × ananassa) and showed different grades of antagonism against 20 fungal pathogens of berries, based on confrontation assays, due to the action of its diffusible and volatile compounds. These fungal pathogens were isolated from decayed strawberry, blackberry, and blueberry fruit and were characterized through internal transcribed spacer (ITS) sequencing and homology searches, exhibiting similarity with well-known postharvest pathogens such as Botrytis, Fusarium, Gotrichum, Mucor, Penicillium, Alternaria, and Botryosphaeria. Koch's postulates were confirmed for most pathogens by re-infecting berry fruit. SER3 showed good capacity to inhibit the growth of Botrytis cinerea and Fusarium brachygibbosum in strawberry fruit, affecting mycelial development. To gain better understanding of the genetic and metabolic capacities of the SER3 strain, its draft genome was determined and was found to comprise a single chromosome of 5.08 Mb, 52.8% G + C content, and 4545 protein-coding genes. Phylogenetic analysis indicated that the SER3 strain is affiliated with the R. badensis species, with an average nucleotide identity > 96% and a genome-to-genome distance > 70%. Comparison of the genomic properties of R. badensis SER3 and other close bacterial relatives showed several genes with potential functions in biocontrol activities, such as those encoding siderophores, nonribosomal peptide synthetases, and polyketide synthases. This is the first study to demonstrate a novel role of the recently discovered R. badensis species (and any other species of the genus Rouxiella) as a biocontrol agent against postharvest fungal pathogens.